Comprehensive protection and revitalization of Levuka world heritage from the perspective of marine spatial planning - Kang, Wanchao; Teng, Xin; Zhao, Qiwei; Pratap, Arpana; Meng, Xue; Zhang, Panpan (Frontiers in Marine Science, 2025)
The protection and development of World Heritage Sites are of great significance for inheriting human civilization, and it is crucial to maintain and enhance their brand quality. Located in a coastal area, the Levuka Historical Port Town currently faces issues such as damage of world heritage and lagging overall development. From the perspective of marine spatial planning, this paper analyzes the conflicts and synergies between land and sea uses, formulates corresponding compatibility rules, and takes blocks as basic units to measure the compatibility and functional optimization strategies between various activities, exploring effective means of achieving comprehensive protection and revitalization of world heritage. The results show that the Levuka Historical Port Town has a good overall compatibility between land and sea uses, but its land use mixing degree is low, with great potential for revitalization. Using marine spatial planning, the Levuka Historical Port Town is divided into a protection zone, an optimization zone, a function expansion zone and a function integration zone. it is necessary to reasonably control activities that threaten relics, promote activities conducive to the development of relics, moderately introduce other functions, increase the vitality of World Heritage Sites, and promote sustainable development of world heritage.